INTEGRATING AUGMENTED REALITY IN ENGLISH LANGUAGE TEACHING :TRENDS IN INDONESIA FROM 2019 TO 2023 - Rosyidah, Umniyah Juman; Anugerahwati, Mirjam (English Review: Journal of English Education, 2024)
Technology 5.0 leads to the technological implementation to help humans, including in terms of ELT. Augmented reality provides students to combine the virtual and real situations to maximize English language acquisition. Therefore, the implementation strategies of AR-ELT implementation need to be conducted. Besides, understanding the ways for implementing AR in ELT helps Indonesian teachers make informed decisions about when and how to implement AR technology into their English teaching. This research conducts systematic literature review to discover the level of education, how it is implemented, and what recommendation of AR-ELT implementation. The results show that elementary students with vocabulary teaching method as the most aspect taught. The implementation of AR-ELT can integrate appropriate teaching approach, blend it with the language learning between online and offline class, combining with another physical media, apply the AR-English implementation with non-English materials. The most important recommendation due to the implementation is that all parties in the institutions must support. Further Indonesian academics need to developed AR app and implement comprehensively in English language learning, so that academics do not only develop AR app without the implementation.